RELATIONS WITH TOTAL CONTENT OF ORGANIC MATTER IN THE AREA MANGROVES ABUNDANCE OF PHYTOPLANKTON IN TANJUNG BALAI ASAHAN WATERS OF NORTH SUMATRA - Joenathan Sarumpaet; Irvina Nurrachmi; Sofyan Husein Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT The purpose of this study to determine the content of organic matter, knowing the abundance of phytoplankton in the waters of Tanjung Balai Asahan, and determine the relationship between total organic matter content of the abundance of phytoplankton in the waters of Tanjung Balai Asahan. This study was conducted in July - August 2019, The method used in this study is a survey method. Observation station determined by purposive sampling. Results of water quality measurements showed that the temperature of between 29.5 to 33 ° C, pH 6-7, 23-25 ppt salinity, brightness ranged from 24.25 to 49.8 cm, the average flow velocity ranges from 0.15 to 0, 48 m / sec, and a depth ranging from 2.7 to 6 m. The survey results revealed thattotal organic matter content ranged20.44 to 27.14 mg / l, Phytoplankton are found there are 6 genus of phytoplankton that is, Isthmia sp, Navicula sp, sp Pleurosigma, Skeletonema sp, Coscinodiscus sp, sp Triceratium, Average - Average abundance of phytoplankton ranged1930.19 -3603.03 ind / l, Total organic matter content relationships with an abundance of phytoplankton have a strong relationship with the coefficient (r) = 0.80, where the increase in total organic matter content of the abundance of phytoplankton will increase. Keywords: Phytoplankton, Total Organic Ingredients, Water Tanjung Balai